Electronic Commerce and Trademarks: Overview of Civil Legal Responsibilities in the Digital Age - Ferry Susanto Limbong; Lily Maryam Nasution (Faculty of Law, Universitas Pekalongan, 2023)
This study aims to analyze electronic commerce and trademarks in terms of civil law responsibilities in the digital era. In this study, the normative juridical research method was used, namely an approach in legal research that focuses on the analysis of written legal sources, such as laws, statutory regulations, court decisions, and other legal documents. The results of the study show that electronic commerce (e-commerce) and trademarks are two aspects that have implications for civil law responsibility. First, electronic commerce is the activity of buying and selling goods and services carried out electronically via the internet or other electronic media. In this context, civil law responsibilities relate to obligations and responsibilities between parties involved in e-commerce transactions, namely as follows: 1) Contracts and Obligations; 2) Consumer Protection; 3) Product Responsibility: Second, a trademark is a symbol or sign used to differentiate the products or services of one company from another. Trademark protection is part of the civil law that protects the rights of brand owners against the use or infringement of said mark as follows: 1) Trademark Registration; 2) Trademark Infringement; 3) Brand Dispute Resolution.